‘Because we are all Europeans!’ When do EU Member States use normative arguments? - Reinhard, Janine (My University, 2012)
Recent debate has highlighted the importance of communication and arguments to explanations of the progress and results of international negotiations. Various studies have indicated that member states taking part in EU negotiations do indeed use arguments, either owing to a normative conception of arguing as a ‘truth seeking discourse’ or a conception of strategic arguing. We also know that contextual conditions, such as the extent to which negotiations are publicized, or the characteristics of the issue being negotiated, affect the degree of arguing. This contribution takes a different view, focusing on actor-specific use of arguments. I find that some member states are more inclined to use arguments than others and try to find explanations that could account for this variation. I hypothesize that the availability of power resources derived from bargaining theory should affect the use of arguments. The subject under investigation here is the EU Intergovernmental Conference leading to the Treaty of Amsterdam (1997). By means of an automated content analysis of member states' position papers, I show that member states who have good alternatives to the agreement being negotiated are less likely to use arguments.
Keywords: 320